(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
The patterns and trends in the integrative development of education, science, technology and production, the preparation of students for creative activity on the basis of technological education, the conceptual and scientific-methodological foundations of the problems of the development of technical creativity in them studied to one degree or another.